The Influence of Member Savings and Loans on the Financial Growth of KSU Putra Daha Liang Anggang - Sulamiatin, Sulamiatin; Asnan, Asnan (Jurnal Ilmu Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of member savings and loans on the financial growth of KSU Putra Daha Liang Anggang, South Kalimantan. The research data consists of financial reports for 2015–2017 using a purposive sampling method. The independent variables are member savings and loans, while the dependent variable is financial growth as measured by assets, capital, business volume, and Net Operating Income (SHU). The analysis used includes descriptive analysis, classical assumption tests, simple linear regression, and multiple regression. The results of the analysis show that member savings fluctuated, increasing sharply in 2016 but decreasing in 2017. Although savings increased, the cooperative's capital actually decreased, indicating the presence of other factors such as operational expenses and SHU distribution. Simple linear regression found a very strong but negative relationship between savings and capital (R² = 0.99; coefficient –0.378). Multiple regression analysis proves that savings and loans have a significant simultaneous effect on cooperative financial growth with an R² of 0.82. The study confirms that member savings and loans are important components for cooperative growth, but their success is influenced by the effectiveness of credit risk management and operational efficiency. Therefore, strategies for collecting savings, improving loan management, and controlling operational costs need to be improved to support the sustainable growth of cooperatives.